Evaluation of the utilization of the preanaesthetic clinics in a University teaching hospital - Merritt-Charles Lorna; Chen Deryk; Hariharan Seetharaman (BMC, 2006)
Abstract Background Dedicated out-patient preanaesthetic clinics are relatively recent phenomenon and information is sparse from developing world. This study attempted to evaluate the utilization of adult and paediatric preanaesthetic clinics and its impact on the cancellations of surgery in Trinidad. Methods All patients scheduled to have elective surgery during the period of twelve weeks were enrolled for prospective collection of data including demographics, the admitting diagnoses, surgical procedure, category of surgery and specialty, and the patients' attendance to preanaesthetic clinics. Cancellations on the day of surgery along with reasons were recorded. The difference between patients who attended and did not attend the clinic was analysed. Results Of 424 patients scheduled for procedures during the study period, 213 were adults and 211 were children. Overall 39% of adults and 46% of the children scheduled for surgery had previously attended the preanaesthetic clinic. Among adults, general surgery patients were the largest majority to attend the preanaesthetic clinic. The paediatric preanaesthetic clinic was mostly utilized by paediatric general surgery. Overall 30% of procedures in adults and 26% of those in children were cancelled. There was a statistically significant difference in cancellations between patients who attended and did not attend the preanaesthetic clinic (p = 0.004). There was a 52% more chance of the procedure getting cancelled if the patient did not attend the clinic. Conclusion The study highlights the inadequate use of the preanaesthetic clinics and the impact of the clinics on last-minute cancellations.